Young Muslims and Christians in a secular Europe: pursuing religious commitment in the Netherlands - Beekers, Daan (Bloomsbury Academic, 2021)
1. Introduction: a comparative anthropology of religious commitment -- 2. Becoming committed -- 3. Authentic submission and moral self-scrutiny -- 4. Doubt, community, and conviction -- 5. Fitting God in -- 6. Distraction, habituation, and closeness to God -- 7. Conclusion.